Remedial colon hydrotherapy device enema as a salvage strategy for inadequate bowel preparation for colonoscopy: A retrospective cohort study - Dongxuan Zhang; Chunxia Zhao; Yuan Tao; Jiao Zhang; Qisheng Zhang; Da Li; Ping Ye; Xiaobo Yu; Chao Chen (PLoS ONE, 2025)
Objective Colon hydrotherapy devices serve as a physiotherapeutic modality to manage colonic disorders by promoting intestinal peristalsis and enhancing gastrointestinal functionality. This study aims to assess and compare the effectiveness, safety, and tolerability of two remedial strategies for inadequate bowel preparation: colon hydrotherapy device enema and oral polyethylene glycol electrolyte powder. Methods A retrospective analysis was performed on 109 patients who failed to adequately prepare for colonoscopy. These patients received remedial bowel preparation on the same day as their procedure, with 55 undergoing colon hydrotherapy enema and 54 receiving oral polyethylene glycol electrolyte powder. Patient satisfaction and tolerance were evaluated through telephone follow-up. Key metrics included the Boston Bowel Preparation Scale scores, preparation time, incidence of adverse reactions, and patient tolerance and satisfaction. Results No significant differences were observed in baseline characteristics between groups (P >  0.05). The Boston Bowel Preparation Scale scores for the entire colon were 7 (3) in the hydrotherapy group and 6.5 (1) in the oral group (z =  -2.075, P =  0.038). Notably, scores for the left colon were significantly higher in the hydrotherapy group [3 (1) vs. 2 (0), z =  -5.586, P <  0.001]. The hydrotherapy group also exhibited a shorter preparation time [80 (20) min vs. 92.5 (20) min, z =  -3.961, P <  0.001] and a lower incidence of adverse effects (36.4% vs. 88.9%, χ² =  32.035, P <  0.001). Patient satisfaction metrics, including re-selection rates and tolerance of side effects, were significantly higher in the hydrotherapy group. Conclusions The colon hydrotherapy device enema is an effective, efficient, and well-tolerated method for bowel cleansing, demonstrating a low incidence of adverse events. It is recommended as an effective and safe remedial therapy for patients with inadequate bowel preparation prior to colonoscopy.